1999
DOI: 10.1097/00000539-199908000-00046
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Desflurane on the Nervous System

Abstract: We used neurophysiological techniques to assess the effects of desflurane on spinal cord conduction and excitability, motor and sensory peripheral nerve conduction, and neuromuscular transmission. Our data demonstrate that desflurane acts preferentially at the level of the spinal motoneuron, providing useful information for neurophysiological monitoring and immobilization during surgery and for minimum alveolar anesthetic concentration definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The mechanism by which inhalational anesthetics potentiate the effects of muscle relaxants is unknown. The proposed mechanisms include a central effect on alpha-motor neurons and interneuronal synapses [8], inhibition of postsynaptic nicotinic acetylcholine receptors [9], or augmentation of the antagonist’s affinity at the receptor site [10]. In addition, more than one mechanism is simultaneously involved and different inhalational anesthetics may not act exactly in the same way [11].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which inhalational anesthetics potentiate the effects of muscle relaxants is unknown. The proposed mechanisms include a central effect on alpha-motor neurons and interneuronal synapses [8], inhibition of postsynaptic nicotinic acetylcholine receptors [9], or augmentation of the antagonist’s affinity at the receptor site [10]. In addition, more than one mechanism is simultaneously involved and different inhalational anesthetics may not act exactly in the same way [11].…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral axons of motor neurones distal to the spinal cord probably do not contribute to immobility, nor do actions at the neuromuscular junction. 49 Conduction in large-diameter myelinated axons, like that in motor neurones, is not sensitive to anaesthetic agents at concentrations relevant to MAC, as many studies have shown. Moreover, conduction in primary sensory nerve axons is relatively unaffected, although impulse generation at peripheral nociceptors may be modi®ed.…”
Section: Cellular Sites Of Anaesthetic Action Within the Spinal Cordmentioning
confidence: 99%
“…Our results show that sevoflurane had no effect on LSR or orbicularis oculi M wave latencies, indicating that up to 1 MAC sevoflurane did not affect nerve conduction velocities which is in agreement with previous studies. 33,34 This result is further inconsistent with the peripheral hypothesis of LSR because ephaptic transmission is facilitated by conduction slowing. 9 However, we cannot completely rule out the peripheral theory of the LSR because we did not investigate the effect of high concentrations of sevoflurane used for > 30 minutes on latency.…”
Section: Discussionmentioning
confidence: 67%